2012
DOI: 10.5005/jp-journals-10026-1017
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Towards Immunization among Dentist of Bhopal City

Abstract: Introduction: Health care workers are at the particular risk of several vaccine preventable diseases due to lack of knowledge or casual attitude toward infection. Which leads to a substantial percentage of morbidity and mortality among patients and dentist as well. Materials and methods: Self-administered structured, coded questionnaire was distributed to 200 private practitioners and teaching staff in all the dental colleges in Bhopal city. Results: Half of them are HBV vaccinated and only 27% of them are awa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…In the present study, male dental practition-ers (80%) were comparatively higher in proportion compared to the female practitioners (20%) which is in accordance to the study conducted by Emir Yüzbasioglu et al (2), R. Sudhakara Reddy (7) and Mohammad Ahmad Al-Omari (8). On the contrary, the study conducted by Vidhatri Tiwari et al (4) revealed that most of the practitioners were females. In this study, higher percentage of practitioners have received vaccination against Hepatitis B (82%) which is in accordance with a study conducted by Veronesi L et al (2004) (9).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In the present study, male dental practition-ers (80%) were comparatively higher in proportion compared to the female practitioners (20%) which is in accordance to the study conducted by Emir Yüzbasioglu et al (2), R. Sudhakara Reddy (7) and Mohammad Ahmad Al-Omari (8). On the contrary, the study conducted by Vidhatri Tiwari et al (4) revealed that most of the practitioners were females. In this study, higher percentage of practitioners have received vaccination against Hepatitis B (82%) which is in accordance with a study conducted by Veronesi L et al (2004) (9).…”
Section: Discussionmentioning
confidence: 89%
“…Effective infection control strategies are intended to break one or more of these links in the chain, thereby prevent¬ing infection (2,3). It has been found that dentists were three times more likely at risk than the general popula¬tion to contract hepatitis B (4). With the emergence of the AIDS epidemic in the 1980s, even more stringent precautions be-came necessary to effectively protect health care workers and the public, leading to the recommendations by the U.S. Centers for Disease Control and Prevention (CDC) concerning the pre¬vention of HIV transmission in health care settings (5).…”
mentioning
confidence: 99%